School Based Counsellor Training: An Evolving Model - Borgen, William A. (Canadian Journal of Counselling and Psychotherapy, 2012)
The development of a counsellor training centre based in a junior secondary school and operated jointly by the University of British Columbia and the Richmond School Board is described. An evaluation of the centre's operation is made in terms of issues in school counselling, issues related to counsellor education, and the training experiences offered.